2018
DOI: 10.1103/physrevb.98.184505
|View full text |Cite
|
Sign up to set email alerts
|

Fraunhofer response and supercurrent spin switching in black phosphorus with strain and disorder

Abstract: We develop theory models for both ballistic and disordered superconducting monolayer black phosphorus devices in the presence of magnetic exchange field and strain. The ballistic case is studied through a microscopic Bogoliubov-de Gennes formalism while for the disordered case we formulate a quasiclassical model. Utilizing the two models, we theoretically study the response of supercurrent to an externally applied magnetic field in two-dimensional black phosphorus Josephson junctions. Our results demonstrate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 67 publications
5
49
0
Order By: Relevance
“…As recently demonstrated, control of these parameters is possible by, for example, applying strain to the system. [9][10][11] To further shed light on the symmetry profiles of these superconducting correlations, in Figs. 1-3, we present a few representative profiles for the real and imaginary parts of the equal-Pspin and opposite-Pspin components as a function of the momenta k x and k y .…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
See 3 more Smart Citations
“…As recently demonstrated, control of these parameters is possible by, for example, applying strain to the system. [9][10][11] To further shed light on the symmetry profiles of these superconducting correlations, in Figs. 1-3, we present a few representative profiles for the real and imaginary parts of the equal-Pspin and opposite-Pspin components as a function of the momenta k x and k y .…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
“…Such situations can be precisely determined by first-principles calculations; e.g., when the system experiences external strain or is subject to doping and intercalation. A practical example is when a black phosphorus mono- layer is under the application of an external strain, as was recently discussed [9][10][11] . The band-structure parameters were obtained using density-functional-theory computations, and symmetry calculations demonstrated that the momenta coefficients can change sign depending on the strength and direction of the applied in-plane strain.…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Weyl semimetals with their Weyl cones tilted to the Fermi surface, namely type-II Weyl semimetals, are also of great interest. [50] Due to their unconventional Fermi surface structure, modification of magnetic quantum oscillations, [51] superconductivity, [52][53][54][55][56][57][58][59][60] optical activity, [61][62][63][64] etc., have been expected and observed in type-II Weyl semimetals.…”
Section: Introductionmentioning
confidence: 99%